ANALYSIS OF SAIFI, SAIDI, CAIDI, AND ENS VALUES AS RELIABILITY INDICES IN THE 20 KV DISTRIBUTION NETWORK AT PT. PLN (PERSERO) UP3 BANDUNG ULP CIJAWURA - Dina Wulansari; Anira Marsha Wahyuni; Riska Mutiara Fitri (Peneliti.net, 2026)
The reliability of the electrical power distribution system is an important factor in ensuring continuity and quality of service to customers. This study aims to analyze the reliability level of the 20kV distribution network at PT. PLN (Persero) UP3 Bandung ULP Cijawura using the System Average Interruption Frequency Index (SAIFI), System Average Interruption Duration Index (SAIDI), Customer Average Interruption Duration Index (CAIDI), and Energy Not Supplied (ENS) indices. The methods used include collecting data on outages, outage duration, the number of affected customers, and the load during the period from January to December 2024. The data was analyzed quantitatively and compared with the SPLN 68-2:1986 and IEEE Std 1366-2003 standards. The calculation results show a SAIFI value of 2.14 times/customer/year, a SAIDI of 2.34 hours/customer/year, a CAIDI of 1.09 hours/time, and an ENS of 84,657 kWh with an estimated economic loss of IDR 122,303,968 per year. Based on a comparison with the standards, the SAIFI and SAIDI values have met the SPLN standard but have not yet met the IEEE standard, while the CAIDI value has met the IEEE standard. The analysis results show that the high frequency and duration of disturbances are influenced by natural factors, third-party activities, animals, and network component conditions. Therefore, preventive and corrective maintenance needs to be improved in order to reduce the disturbance index values and increase the reliability of the distribution system.